Acupuncture for blunt chest trauma: A protocol for a double-blind randomized control trial. Issue 18 (7th May 2021) - Kao, Pei-Yu; Ben-Arie, Eyal; Lu, Ting-Yu; Ho, Wen-Chao; Lee, Yu-Chen; Lin, Yu-Sen; Chen, Chien-Kuang; Chen, Jian-Xun; Huang, Tzu-Min; Chen, Fang-Pey
Abstract: Introduction: Blunt chest trauma (BCT) accounts for up to 65% of polytrauma patients. In patients with 0 to 2 rib fractures, treatment interventions are typically limited to oral analgesics and breathing exercises. Patients suffering from BCT experience symptoms of severe pain, poor sleep, and inability to perform simple daily life activities for an extended period of time thereafter. In this trial, we aim to investigate the efficacy of acupuncture as a functional and reliable treatment option for blunt chest trauma patients. Methods: The study is designed as a double-blind randomized control trial. We will include 72 patients divided into 2 groups; the acupuncture group (Acu) and placebo group (Con). The acupuncture group will receive true acupuncture using a uniquely designed press tack needle. The control group will receive placebo acupuncture treatment through the use of a similarly designed press tack needle without the needle element. The acupoints selected for both groups are GB 34, GB 36, LI 4, LU 7, ST 36, and TH 5. Both groups will receive 1 treatment only following the initial visit to the medical facility and upon diagnosis of BCT. Patient outcome measurements include: Numerical Rating Scale, Face Rating Scale, respiratory function flowmeter, Verran Snyder-Halpern sleep scale, and the total amount of allopathic medication used. Follow-up time will be scheduled at 4 days, 2 weeks, and lastly 3 months. Expected outcome: The results of this study can potentially provide a simple and cost-effective analgesic solution to blunt chest trauma patients. This novel study design can serve as supporting evidence for future double-blind studies within the field of acupuncture. Other information: The study will be conducted in the thoracic surgical department and acupuncture department in China Medical University Hospital, Taichung, Taiwan. The study will be conducted on blunt chest trauma patients and is anticipated to have minimum risk of adverse events. Enrollment of the patients and data collection will start from March 2020. Study completion time is expected in March 2022. Protocol Registration: (CMUH109-REC1-002), (NCT04318496).